2016
DOI: 10.1371/journal.pone.0152758
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Semicarbazide-Sensitive Amine Oxidase Stabilizes the Established Atherosclerotic Lesions via Inducing the Phenotypic Switch of Smooth Muscle Cells

Abstract: Given that the elevated serum semicarbazide-sensitive amine oxidase (SSAO) activity is associated with the severity of carotid atherosclerosis in clinic, the current study aims to investigate whether SSAO inactivation by semicarbazide is beneficial for established atherosclerotic lesions in LDLr knockout mice on a high-fat/high- cholesterol Western-type diet or after dietary lipid lowering. Despite no impact on plasma total cholesterol levels, the infiltration of circulating monocytes into peripheral tissues, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 26 publications
1
12
2
Order By: Relevance
“…In the present study, VAP-1/SSAO inhibition by PXS-4728A significantly reduced atherosclerosis, which was different from previous reports in other animal models 17 , 18 . In LDL receptor knock-out mice, 3 or 6 weeks of SSAO inhibition by semicarbazide after feeding western diet for 6 or 9 weeks promoted the switch of SMC from a contractile phenotype to a synthetic phenotype and increased the accumulation of collagens and the thickness of cap, thereby enhancing plaque stability.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the present study, VAP-1/SSAO inhibition by PXS-4728A significantly reduced atherosclerosis, which was different from previous reports in other animal models 17 , 18 . In LDL receptor knock-out mice, 3 or 6 weeks of SSAO inhibition by semicarbazide after feeding western diet for 6 or 9 weeks promoted the switch of SMC from a contractile phenotype to a synthetic phenotype and increased the accumulation of collagens and the thickness of cap, thereby enhancing plaque stability.…”
Section: Discussioncontrasting
confidence: 99%
“…In LDL receptor knock-out mice, 3 or 6 weeks of SSAO inhibition by semicarbazide after feeding western diet for 6 or 9 weeks promoted the switch of SMC from a contractile phenotype to a synthetic phenotype and increased the accumulation of collagens and the thickness of cap, thereby enhancing plaque stability. However, there was no significant difference in plasma TC and plaque size between the treatment and the placebo group 18 , which was different from the findings of our study. Furthermore, if semicarbazide was administered simultaneously with western diet, it inhibited the migration of circulating monocytes into peripheral tissue and aggravated the development of atherosclerosis 17 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Here, we found that treatment with LJP1586 led to a significant reduction in the density of macrophages in atherosclerotic plaques in mice, suggesting that VAP-1 is a potential target for therapeutics aimed at reducing inflammation associated with atherosclerosis. These results are in the line with previous mouse studies using a prototypic SSAO inhibitor, semicarbazide (also inhibiting lysyl oxidases and thus not being specific for VAP-1), as a treatment 29 30 . Mice with pre-existing, advanced atherosclerotic plaques were treated with VAP-1-targeted small molecule LJP1586 that probably explains that the short-term therapy at this stage had no effect on the size/amount of plaques.…”
Section: Discussionsupporting
confidence: 92%
“…So far, there are limited studies that investigate the effects of VAP-1/SSAO inhibition on atherosclerosis. [26][27][28] Two of them used semicarbazide to inhibit VAP-1/SSAO activity in LDL receptor knock-out mice, with conflicting results. In one report, semicarbazide aggravated atherosclerotic lesions.…”
Section: Introductionmentioning
confidence: 99%